READINESS OF PRESCHOOL TEACHERS OF EARLY AGE AND PRESCHOOL CHILDREN TO CREATE ART-COMMUNICATION CLUSTERS - Olena Polovina; Iryna Novoseletska (Borys Grinchenko Kyiv Metropolitan University, 2024)
The article examines the issue of preschool teachers professional training, its artistic component in particular. The need for an innovator teacher's training who, in accordance with the pace of world changes, is ready to modernize the educational process, has been updated; a conscious understanding of the education of a creative, free and multifaceted personality by introducing it to the world of art and possesses the necessary methodological tools. It was noted that an artistic interaction with preschool age children needs a modified logical and sequential support. A theoretical analysis of studying an issue of artistic and creative interaction between teachers and early and preschool age children in native and foreign scientific literature is presented. The position of the need to form preschool children's artistic and creative competence through appealing to their sensory sphere, and the development of empathy is substantiated. The toolkit for tasks implementation of early age and preschool children art-world is revealed, namely, art communication is characterized as a form of integrated interaction between an adult and a child, which contains elements of an artistically productive, musical, theatrical component and in which any of these components can dominate or unfold separately. Effective means of preschool teachers training to conduct art-communication have been determined, in particular, clusters of art-communication (mind map) have been identified according to the algorithm «I hear - see - feel - know - act». The results of the ascertainment stage of the research on the readiness of creation and implementation of art-communication clusters in the educational process of kindergarten by preschool teachers are described. The criteria for the formation of the skills of moderating clusters of art communication by teachers of kindergarten are outlined: motivational-emotional, knowledge-theoretical, reflective-empathetic, practical-active. Empirical research methods are quantitatively and qualitatively characterized: questionnaires using Google form online resource; a method of pedagogical observation of teachers' activities; an interviewing. It was found out that the middle (lateral - close to the middle) and low (juvenile - hidden) levels prevail among the respondents.